THE INFLUENCE OF TOTAL QUALITY MANAGEMENT (TQM) APPLICATION ON OPERATIONAL PERFORMANCE ON UD. "MATAHARI" TEMPE CRACKERS. RESTU JAYA - Ringga Arisgi Wiyono; Fien Zulfikarijah; Iqbal Ramadhani Fuadiputra (JEES: Journal of Economic Empowerment Strategy, 2023)
For a company the best way to maintain optimal company conditions is to implement Total Quality Management (TQM). This study aims to determine the effect of implementing Total Quality Management (TQM) which is then realized in 4 basic pillars, namely customer focus, employee empowerment, continuous quality improvement, and fact-based management on operational performance at UD. Restu Jaya. The research sample used was 44 employees. Methods of data analysis using multiple linear regression, classical assumptions, and hypothesis testing. Based on the results of data analysis, the implementation of Total Quality Management (TQM) is proven to have a simultaneous effect on operational performance variables. However, there are several variables that have no partial effect on the operational performance variable, while those variables are employee empowerment and continuous quality improvement. While the variables focused on customers and management based on facts have a significant partial effect on operational performance variables